PURCHASE DECISION AFFECTS, PRICE, PRODUCT QUALITY AND WORD OF MOUTH - Muhammad Arif; Ilham Khairi Siregar (International Journal of Economic, Technology and Social Sciences (Injects), 2021)
This study aims to identify and analyze the effect of product quality, price and word of mouth on the purchasing decision of Milkita Candy. This study uses marketing management theory with variables (product quality), (price), (word of mouth) and variables (purchase decisions). Researchers determine the population, namely all consumers who decide to buy dairy products. The sampling technique, or non-probability sampling, is used to determine the number of samples. The sample size for this survey is 69 respondents. On the other hand, evaluation, data analysis techniques mostly use linear regression analysis. Based on the results of data analysis, it can be concluded that the product quality variable has a partial effect on purchasing decisions because the product quality variable is important. Second, we can conclude that the price variable has a partial effect on purchasing decisions because price is very important. In addition, the word of mouth variable is also important, so it can be concluded that the word of mouth variable has a positive and significant effect on purchasing decisions. In addition, an important conclusion is taken simultaneously that the variables (product quality), (price) and (word of mouth) have a large influence on the variable (purchase decision) at the same time. Based on the results of data analysis, companies are advised to make alternative pricing strategies that are better and pay attention to the quality of product offerings before the products are distributed. For consumers. The word of mouth variable is also important, so it can be concluded that the word of mouth variable has a positive and significant effect on purchasing decisions. In addition, an important conclusion is taken simultaneously that the variables (product quality), (price) and (word of mouth) have a large influence on the variable (purchase decision) at the same time. Based on the results of data analysis, companies are advised to make alternative pricing strategies that are better and pay attention to the quality of product offerings before the products are distributed. For consumers. The word of mouth variable is also important, so it can be concluded that the word of mouth variable has a positive and significant effect on purchasing decisions. In addition, an important conclusion is taken simultaneously that the variables (product quality), (price) and (word of mouth) have a large influence on the variable (purchase decision) at the same time. Based on the results of data analysis, companies are advised to make alternative pricing strategies that are better and pay attention to the quality of product offerings before the products are distributed. For consumers. (price) and (word of mouth) have a great influence on the variable (purchase decision) at the same time. Based on the results of data analysis, companies are advised to make alternative pricing strategies that are better and pay attention to the quality of product offerings before the products are distributed. For consumers. (price) and (word of mouth) have a great influence on the variable (purchase decision) at the same time. Based on the results of data analysis, companies are advised to make alternative pricing strategies that are better and pay attention to the quality of product offerings before the products are distributed. For consumers.